MANUSIA MAKHLUK YANG DIISTIMEWAKAN - Azizah, Sahara Puan; Nadhila, Nadhila (Proceeding International Seminar of Islamic Studies, 2024)
The most perfect creatures created by Allah are humans, creatures with the highest rank compared to other creatures created by Allah. Because humans are given the advantage of reason and thoughts so they can differentiate between good and bad, especially humans in living and caring for themselves. Compared to other creatures humans have been given many advantages by Allah SWT. “and we preferred them over most of the creatures that we have created with perfect advantages “(QS. 17/AL Isra’:70). The human form was perfected,”And He formed you and perfected  your form”.(QS. 40/AL Mu’min 64) Human needs have been provided “and for you a residence on earth, and enjoyment until the the appointed time”. (QS. 2/AL Baqarah: 36). Humans as we understand them are God’s most special creatures, the best of God’s creations with all the advantages and virtues given by God. The onlycreatures capable of receiving the almighty’s trust. Therefore, let us use this God-given potential to compete in doing goods deeds.